Peran Pendidikan Masyarakat dalam Mencegah Pernikahan Usia Dini dan Dampaknya: The Role of Community Education in Preventing Early Marriage and its Impacts - Nurwahdaniar Syahrul; Arlin Adam; Andi Nurlinda (Al-Musannif, 2024)
People continue to socialize about the negative impacts of early marriage. However, early marriage still occurs a lot, especially in rural areas. This study aims to examine the factors causing early marriage, the impacts of early marriage, and the role of community education in preventing early marriage. This study uses a qualitative approach with the research location in Labakkang District, Pangkep Regency. Data collected through observation, interviews, and documentation were analyzed descriptively. The informants in this study numbered 5 people: a community leader, three early marriage couples, and an employee of the religious affairs office. The results of the study showed that early marriage was due to arranged marriages and considered a disgrace if they refused the proposal. The social health impacts of early marriage are dropping out of school, gender discrimination, divorce, mental health, pregnancy, childbirth, and postpartum problems. The role of community education in preventing early marriage is still very minimal because of the characteristics of a tough society that make it difficult to provide understanding. This research has implications for the importance of the government, community leaders, religious leaders, and traditional leaders working together to provide education regarding early marriage and its impact on society at large.